Generalized q-Schur algebras and quantum Frobenius - McGerty, K (2007)
The quantum Frobenius map and it splitting are shown to descend to maps between generalized q-Schur algebras at a root of unity. We also define analogs of q-Schur algebras for any affine algebra, and prove the corresponding results for them. © 2007 Elsevier Inc. All rights reserved.